[125I]deoxycytidine used in a rapid, sensitive, and specific assay for herpes simplex virus type 1 thymidine kinase. - Summers, W C (1977)
[125I]deoxycytidine was a good substrate for herpes simplex virus type 1 thymidine kinase (TK), whereas [125I]deoxycytidine was a very poor substrate for cellular TK. Simple, sensitive, and specific assays for viral TK could be carried out in vivo and in vitro even in the presence of cell TK. Autoradiographic detection of incorporated [125I]deoxycytidine provided a rapid and simple method for detection of and screening for viral TK in infected as well as viral TK-transformed cells.